2019
DOI: 10.1074/jbc.rev118.002982
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to disease from natural variations in human cytoplasmic tRNAs

Abstract: Edited by Karin Musier-Forsyth Perfectly accurate translation of mRNA into protein is not a prerequisite for life. Resulting from errors in protein synthesis, mistranslation occurs in all cells, including human cells. The human genome encodes >600 tRNA genes, providing both the raw material for genetic variation and a buffer to ensure that resulting translation errors occur at tolerable levels. On the basis of data from the 1000 Genomes Project, we highlight the unanticipated prevalence of mistranslating tRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 140 publications
0
81
0
Order By: Relevance
“…One example of this is the synergistic effect of a point mutation in tRNA Arg , which enhances neurodegeneration caused by a mutant GTPBP2 gene, a ribosome recycling factor, in mice [27]. The same tRNA Arg mutation is also found in the human population [26]. The hypothesis is further supported by the association of tRNA modifying enzymes and error prone tRNA synthetases with disease.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…One example of this is the synergistic effect of a point mutation in tRNA Arg , which enhances neurodegeneration caused by a mutant GTPBP2 gene, a ribosome recycling factor, in mice [27]. The same tRNA Arg mutation is also found in the human population [26]. The hypothesis is further supported by the association of tRNA modifying enzymes and error prone tRNA synthetases with disease.…”
Section: Discussionmentioning
confidence: 94%
“…tRNA variants that result in loss of function may impact translation fidelity or protein synthesis rates by altering cellular tRNA pools [26]. Eukaryotic tRNAs are transcribed by RNA polymerase III and require internal A and B box promoters for expression.…”
Section: Location Of Variants On the Trna Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, traditionally, protein mistranslation is thought to be harmful or lethal to cells. Indeed, it causes a wide range of human diseases including neurological disorders, developmental disorders, viral infections, and cancers (Schimmel, 2008;Kapur and Ackerman, 2018;Lant et al, 2019;Ou et al, 2019). However, very recently, a number of studies have shown that protein mistranslation is not always detrimental (Pan, 2013;Ribas de Pouplana et al, 2014;Steiner and Ibba, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by Da Vinci’s imagination, a symposium has even been organized on modeling and imaging the whole human body at the atomic scale to understand the human body (). Computational biology has successfully identified disease-linked genes [18,19,20] and harnessed artificial intelligence neuron connectivity and electrical flow to model the brain. The sequencing of individuals has permitted comparisons of corresponding sequences in diseased and healthy tissues, and with the help of computational biology, technological advances have accomplished the imaging and tracking of molecules in action in single cells [21,22,23].…”
Section: Introductionmentioning
confidence: 99%